CORPORATE RIVALRY IN FORD V FERRARI (2019): A STRATEGIC ANALYSIS THROUGH PORTER'S FIVE FORCES AND EXPRESSIVE LITERARY CRITICISM - Nathannielle, Vincent (Universitas Negeri Surabaya, 2025)
This research examines instances of corporate rivalry depicted in the film Ford v Ferrari (2019) and analyzes its impact on the competing automotive companies and the film's main protagonists. The study employs a qualitative interpretive film analysis design, utilizing M.H. Abrams' expressive literary criticism theory to examine the film's authored choices in relation to historical context, while Porter's Five Forces framework serves as the analytical lens for identifying and evaluating competitive dynamics. Primary data consist of timestamped scenes, dialogue excerpts, and screenshots from the film, collected through systematic observation and supplemented by historical documentation. The analysis reveals how corporate rivalry progresses throughout the film, primarily from Ford Motor Company's perspective, through identified competitive forces including threat of new entrants, threat of substitute products, and bargaining power of suppliers and buyers. Findings demonstrate that the rivalry not only shaped the future trajectories, historical legacies, and competitive positions of both companies but also profoundly impacted the personal and professional lives of protagonists Ken Miles and Carroll Shelby during and after the depicted events. The study contributes to the intersection of literary criticism and strategic management by demonstrating how cinematic narratives can serve as pedagogical sites for understanding corporate competitive action sequences.